2014
DOI: 10.1088/0953-2048/27/4/044014
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of anisotropic vortex pinning by intrinsic and irradiation-induced defects in Ba(Fe,Co)2As2studied by quantitative magneto-optical imaging

Abstract: Here we present a study of the pinning properties of high-quality single crystals of Ba(Fe 1−x Co x ) 2 As 2 (x = 0.07) by means of the quantitative magneto-optical imaging (MOI). This technique allows us to measure the magnetic field and supercurrent distribution as a function of the applied magnetic field and temperature, thus extracting the local parameters such as the critical current density, without any model assumption. Since values of the local supercurrent are obtained on the micron scale, we are able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…The T c of the pristine sample is 38. 8 lower than that of the pristine one. Theoretically, perfectly introduced correlated columnar defects do not suppress T c , and it accounts for the weak suppression on T c of the sample with small B U .…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…The T c of the pristine sample is 38. 8 lower than that of the pristine one. Theoretically, perfectly introduced correlated columnar defects do not suppress T c , and it accounts for the weak suppression on T c of the sample with small B U .…”
Section: Methodsmentioning
confidence: 66%
“…It is known that J c in superconductors can be further enhanced by introducing defects using swift particle irradiations [2]. In our previous studies, remarkable effects have been demonstrated in IBS using heavy-ions [3][4][5][6][7][8] and protons [9] into Co-doped Ba-122 single crystals. In these reports, we irradiated heavy-ions such as 200 MeV Au, 800 MeV Xe, and 2.6 GeV U to create columnar defects, which have excellent geometrical matching with vortices, and are expected to be ideal pinning centers.…”
Section: Introductionmentioning
confidence: 93%
“…TEM microscopy revealed that 200-MeV Au-ion irradiation of Ba 1− x K x Fe 2 As 2 crystals results in the formation of defects that are linearly correlated along the ion track but – contrary to the case of high- T c cuprates – due to the metallic nature of the compound, they are discontinuous (30–240 nm in length) 27 . In fact, magneto-optical imaging showed the clear signature of anisotropic flux pinning by discontinuous tracks in crystals irradiated with Au ions at the higher energy of 2 GeV 20 , which are present also with irradiation at lower energies (250 MeV) 29 . Moreover, a significant difference with respect to cuprates emerged from a STM analysis of irradiated Fe(Se,Te) crystals, showing that columnar defects produced by 250-MeV Au-ions have a metallic core 28 , instead of the insulating core of the amorphous tracks that the same ions with the same energy produce in cuprates 30 .…”
Section: Introductionmentioning
confidence: 96%
“…First, the maximum critical field H C2 is very high at low temperatures ( 4 , 5 ), the compounds also exhibit rather isotropic superconductivity. Second, as in the cuprates ( 6 ), J C can be strongly enhanced by high-energy ion irradiation ( 2 , 7 ). Finally, the irradiation leaves T C virtually unchanged to a degree unknown in cuprate high-temperature superconductors.…”
mentioning
confidence: 99%